The effect of perceived organizational support on the prohibitive voice behavior of knowledgeable talents during the COVID-19 pandemic: Exploring moderating role of the digitalization level - Chen, Xiao; Ren, Kangjun; Shen, Yan (Frontiers in Psychology, 2022)
This study focuses on the effect of perceived organizational support on the prohibitive voice of knowledgeable talents and on the factors influencing that voice during the COVID-19 pandemic in China. Grounding our research in social exchange theory and the Chinese sociocultural background, we collected data from 714 questionnaires from universities located in Zhejiang Province and found, first, that perceived organizational support significantly increased the prohibitive voice of knowledgeable talents and, second, that in the relationship between perceived organizational support and the prohibitive voice of those talents, the level of digitalization level of an organization has a positive the effect of perceived organizational support on prohibitive voice behavior. This study enriches the theory of voice behavior and helps universities understand the behavioral patterns of knowledgeable talents to prohibitive voice. This understanding is of practical use in guiding the cultivation of an atmosphere with abundant voice behavior.